2017
DOI: 10.3415/vcot-16-10-0144
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral shoulder arthrodesis in a Pekinese using three-dimensional printed patient-specific osteotomy and reduction guides

Abstract: Patient-specific, three-dimensional printed osteotomy and reduction guides facilitated accurate bilateral shoulder arthrodeses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 20 publications
1
50
0
Order By: Relevance
“…Numerous human and veterinary surgical studies have reported the use of 3D plastic models as surgical guides to use intraoperatively. 14,15,23,24 The 3D-printed specific guide permitted rapid, safe and accurate placement of implants. 15,23,24 In our study, only the size of the 3D model and the impact of the autoclave on it were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous human and veterinary surgical studies have reported the use of 3D plastic models as surgical guides to use intraoperatively. 14,15,23,24 The 3D-printed specific guide permitted rapid, safe and accurate placement of implants. 15,23,24 In our study, only the size of the 3D model and the impact of the autoclave on it were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,23,24 The 3D-printed specific guide permitted rapid, safe and accurate placement of implants. 15,23,24 In our study, only the size of the 3D model and the impact of the autoclave on it were evaluated. The effects of autoclaving could be more detrimental on a surgical guide since both the size and the exact shape of the guide have to be preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Presurgical planning using 3D-printing anatomical models has been adopted in veterinary medicine [4][5][6] and related research [7,8], particularly in orthopaedic surgery, thus improving surgeon con dence and reducing surgical time, the occurrence of surgical complications, and surgeons' exposure to radiation [4,6,8]. These studies have indicated that 3D-printed models are bene cial when used for managing complex cases and when used by inexperienced surgeons [4,6,9]. Additionally, 3D-printed bone models are suitable for presurgical rehearsals of plate contouring, osteotomy, and the design of surgical guides [4,6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have indicated that 3D-printed models are bene cial when used for managing complex cases and when used by inexperienced surgeons [4,6,9]. Additionally, 3D-printed bone models are suitable for presurgical rehearsals of plate contouring, osteotomy, and the design of surgical guides [4,6,7,9]. However, in veterinary orthopaedics, only three studies have evaluated the linear deviation of 3D-printed long-bone models [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) printing or additive manufacturing, previously known as rapid prototyping, is becoming increasingly popular in veterinary medicine as a method of reproducing bone replicas for management of orthopaedic cases. [10][11][12][13][14][15][16][17] In addition, 3D computer-assisted surgical planning (CASP) has many clinical applications in reconstructive surgery in human and veterinary medicine. 9,14,18 To the authors' knowledge, there is no current literature reporting the use of 3D CASP and printing in the repair of an articular fracture in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%